Repulsion effect on superinfecting virions by infected cells for virus infection dynamic model with absorption effect and chemotaxis. (February 2017) - Wang, Wei; Ma, Wanbiao; Lai, Xiulan
Abstract: A mathematical model for virus infection dynamics with absorption effect and chemotaxis is proposed to study the repulsion effect on superinfecting virions by infected cells. The basic reproduction number R 0 is established. Furthermore, we show that the threshold dynamics can be expressed by the basic reproduction number R 0 in a bounded domain. It is shown that the infection-free steady state E 0 is asymptotically stable if R 0 < 1, and the virus is uniformly persistent if R 0 > 1 in the case of spatially heterogeneous infections. The stability properties and Turing instability of the proposed model have been extensively discussed for the case of spatially homogeneous infections. In addition, the existence of the travelling wave solutions is discussed in unbounded domain. At last, numerical simulations are carried out to illustrate the main results.